Penerapan Pendekatan Kontekstual dalam Pembelajaran PAI untuk Meningkatkan Prestasi Belajar Siswa SMP Integrasi Annajiyah Lubuklinggau - Yanti, Rusma; Muhammad Rudi Wijaya; Yayu Tsamrotul Fuada (UNISAN JURNAL, 2025)
This study aims to describe the implementation of the contextual approach in Islamic Religious Education (PAI) learning and to analyze its impact on improving students’ learning achievement at SMP Integrasi Annajiyah Lubuklinggau. Islamic Religious Education plays an essential role in shaping students’ religious, moral, and social character. However, preliminary observations revealed that many students were still less active during the learning process, and their learning outcomes in PAI were not yet optimal. Therefore, it is necessary to apply an innovative learning model that connects the learning material with real-life contexts so that students become more motivated and able to understand Islamic teachings in an applicable way. This study employed a qualitative descriptive approach, with the research subjects consisting of PAI teachers and eighth-grade students at SMP Integrasi Annajiyah Lubuklinggau. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of the contextual approach was carried out through seven main components: (1) constructivism, where students build their understanding of Islamic concepts from real experiences; (2) questioning, to encourage critical and reflective thinking; (3) inquiry, by involving students in explorative activities; (4) learning community, through collaborative group work and discussions; (5) modelling, by demonstrating Islamic moral behavior; (6) reflection, for evaluating students’ understanding and attitudes; and (7) authentic assessment, to measure learning outcomes comprehensively. This approach effectively increased students’ motivation, participation, and achievement, especially in cognitive and affective domains. Supporting factors include the school’s administrative support, the availability of contextual learning media, and teachers’ competence in designing innovative lessons. Challenges faced in implementation involve limited time and varying student learning abilities. Overall, the contextual approach proved effective in enhancing students’ learning achievement and understanding of Islamic values at SMP Integrasi Annajiyah Lubuklinggau. This study is expected to serve as a reference for Islamic Religious Education teachers in developing creative, applicable, and life-relevant learning strategies, ensuring that Islamic education not only focuses on theory but also cultivates moral character and Islamic behavior in daily life.